CuS nanotrough-networks for highly stable transparent conducting electrodes. Issue 21 (26th April 2016) - Zhang, Xiaojia; Guo, Wenxi; Gao, Guoyun; Que, Miaoling; Pan, Caofeng; Wang, Zhong Lin
Abstract : Here, we present a newly designed, highly flexible transparent conductive electrode based on a copper sulfide nanotrough network (CuS NN) film. Abstract : Here, we present a newly designed, highly flexible transparent conductive electrode based on a copper sulfide nanotrough network (CuS NN) film. This electrode achieves the sheet resistance of ∼20 Ω sq −1 with a transmittance of up to 80%, which is produced by a process involving electrospinning, metal deposition and low temperature solvothermal reaction. The novel CuS NN film shows excellent chemical stability, exposed to various conditions of thermal oxidation at 160 °C, humid air with 80% relative humidity at 85 °C, and H2 O2 solution, respectively. During the bending test, the CuS NN electrode exhibited remarkable mechanical stability. We have finished the four wire resistive touch-screen devices based on the CuS NN electrode, which illustrate a promising alternative to traditional TCE materials for wearable electronic devices.